Frequency of Tobbaco use in Different Occupational Groups of Peshawar - Ali, Jabar; Faheem, Mohammad; Gul, Adnan Mehmood; ., Shahzeb; Hafizullah, Mohammad (International Journal of Pathology, 2018)
Background: Tobacco use is rapidly prevailing globally. There is no large scale planned study available to knowthe status of tobacco use in our country.Objective: Estimate the frequency of various forms of tobacco use in different occupational groups of districtPeshawar.Material and method: A total of 2548 subjects belonging to different occupations including both male and femalewere randomly recruited for the study.Results: Out of a total 2548 persons with median age 37 ranged (12-82) years, there were 1799 non-tobacco usersand 749 were taking tobacco in different forms. The overall frequency of tobacco usage in our society wasdetermined as 29.4%. Cigarette smoking is the most popular tobacco used by Pakistani followed by naswar. Thenaswar is highly liked by cooks (31.5%), followed by sweepers (30.3%), prisoners (28.3%), dairy workers (22.42%)and teachers (7.32%).Conclusion: Tobacco use is very common (29.4%) in different occupational groups of Peshawar. The crude and themost dangerous form of tobacco (naswar) is still under use of many people (13.4%).